2012
DOI: 10.1016/j.concog.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Induction of lucid dreams: A systematic review of evidence

Abstract: In lucid dreams the dreamer is aware of dreaming and often able to influence the ongoing dream content. Lucid dreaming is a learnable skill and a variety of techniques is suggested for lucid dreaming induction. This systematic review evaluated the evidence for the effectiveness of induction techniques. A comprehensive literature search was carried out in biomedical databases and specific resources. Thirty-five studies were included in the analysis (11 sleep laboratory and 24 field studies), of which 26 employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
231
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(239 citation statements)
references
References 46 publications
(86 reference statements)
3
231
2
3
Order By: Relevance
“…While this causal connection is important on the neurophysiological level, due to the small effects, tDCS might not be a promising tool for lucid dream induction on a practical level (Noreika et al, 2010). For practical purposes, other lucid dream induction methods can be suggested (Stumbrys, Erlacher, Schädlich, & Schredl, 2012). Future studies could target other brain areas, such as the precuneus, to increase the probability of lucid dreaming, as well as higher stimulation intensities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While this causal connection is important on the neurophysiological level, due to the small effects, tDCS might not be a promising tool for lucid dream induction on a practical level (Noreika et al, 2010). For practical purposes, other lucid dream induction methods can be suggested (Stumbrys, Erlacher, Schädlich, & Schredl, 2012). Future studies could target other brain areas, such as the precuneus, to increase the probability of lucid dreaming, as well as higher stimulation intensities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The participants could use any technique to induce lucid dreams (cf. Stumbrys, Erlacher, Schädlich, & Schredl, 2012), with the exception of drug intake. After becoming lucid in a dream, they had to start immediately practicing the task (repeating the memorised sequence) and continue the practice for as long as possible.…”
Section: Methodsmentioning
confidence: 99%
“…Lucid dreaming induction techniques have been reviewed for their efficacy by Stumbrys et al, (2012) who argue that of the many available, three cognitively-based induction techniques appear promising methods. These are; the Mnemonic Induction of Lucid Dreams (e.g.…”
Section: Lucid Dreaming Inductionmentioning
confidence: 99%
“…Edelstein & LaBerge, 1992;LaBerge et al, 1994). The evidence from Stumbrys et al, (2012) review implies that combined techniques may result in higher reported success rates for the induction of lucid dreams, though these techniques are not without issue (See Stumbrys et al, 2012) it appears the wisest approach for an induction study to adopt.…”
Section: Lucid Dreaming Inductionmentioning
confidence: 99%